Essential law for social workers - Madden, Robert G. (Columbia University Press, 2003)
Whether protecting their own rights or those of their clients, or navigating the juvenile justice, immigration, or welfare systems, social workers confront legal issues every day. This book explores legal concepts, legal reasoning, and legal processes--illustrated with case vignettes from social work practice--in order to provide social work practitioners and students with practical and accessible legal knowledge. It introduces readers to scholarship about the law and to conceptual knowledge that can be applied to any interaction with the legal system. Social workers are thereby enabled to "think like a lawyer" and increase their effectiveness. The volume features a discussion of recent reform movements, including Alternative Dispute Resolution, and an appendix of sources for legal information and research on the law